Integrative Land-Biodiversity-Climate Action: Leveraging Synergies through Ecosystem Restoration in Central Asia - Mirzabaev, Alisher; Akramkhanov, Akmal (Economics of Land Degradation initiative, 2025)
This is the English counterpart of the Central Asia case study. It provides comprehensive analysis of degradation patterns, investment needs, and governance frameworks across the five Central Asian countries. It shows that coordinated land restoration could reduce implementation costs by up to USD 6.2 billion. Policy recommendations focus on MRV harmonization, regional learning exchanges, and private sector mobilization.